RESPON PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) TERHADAP DOSIS PUPUK UREA - Apriastuti, Ni Putu Eka; Putra, Anak Agung Gede; Karnata, I Nengah (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
Water spinach is a plant whose results are sought in the form of leaves and stems. This study aims to determine the response of land kale plant growth to doses of urea fertilizer. The research was conducted in the experimental garden of the Agrotechnology Study Program, Faculty of Science and Technology, University of Tabanan. The research was carried out from 31 December 2021 to 30 January 2022. This research was an experiment in polybags using a Randomized Block Design (RBD) with one factor and repeated 4 times. The results showed that the dose of urea fertilizer significantly affected the total oven dry weight of plants with the highest value obtained at a dose of 2 g (U4) urea fertilizer of 1,27 and the lowest total oven dry weight of plants at a dose of urea fertilizer 0 g (U0) of 0,13 g.